Occupational Health in Nursing 2018
DOI: 10.1136/oemed-2018-icohabstracts.1000
|View full text |Cite
|
Sign up to set email alerts
|

1137 Perceptions of the use of technology in a blended learning occupational health nursing programme in durban, south africa

Abstract: Introduction Violence in hospitals is a serious occupational health and safety (OHS) issue affecting the physical and mental health of front line staff, as well as, the quality of patient care. In 2010, the province of Ontario (Canada) introduced legislation that directs hospitals to put into place violence prevention and management systems. Our study examined how five Ontario hospitals have developed and implemented their violence prevention programs. Methods Semi structured interviews were conducted with eig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…However, the use of the BL approach in pre-service health education programs poses major challenges, such as lack of knowledge and skills among educators as well learners, hard and soft infrastructure facilities including internet connections and computers in most universities. [31][32][33] The BL approach became an important alternative to the traditional teaching when the COVID-19 pandemic started in Rwanda. BL enabled the continuity of teaching while respecting preventive measures against the pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the use of the BL approach in pre-service health education programs poses major challenges, such as lack of knowledge and skills among educators as well learners, hard and soft infrastructure facilities including internet connections and computers in most universities. [31][32][33] The BL approach became an important alternative to the traditional teaching when the COVID-19 pandemic started in Rwanda. BL enabled the continuity of teaching while respecting preventive measures against the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are several challenges encountered by HLIs in low-resource countries, such as internet connectivity and computers to be used for BL. [5,31,32,34] Since BL was new to some HLIs and others have encountered several challenges, there was a need to conduct a study that documents the students' perceptions about BL in Rwanda. Therefore, this study explored the nursing and midwifery students' perceptions and experiences of using BL in HLIs in Rwanda.…”
Section: Introductionmentioning
confidence: 99%
“…The American Association of Colleges of Nursing reports that nurses are the late adopters of technology, with their increasing age regarded as an important contributing factor to this delay. Orton et al (2015) report that computer anxiety in nurses interferes with the adoption of electronic learning. Almost all of the participants disagreed that they get a sinking feeling when they think of trying to use e-learning.…”
Section: Nurse Educators' Attitudes To Using Technologymentioning
confidence: 99%
“…A trend was observed that in some studies the third-generation cultural-historical activity theory (Engeström, 1987) is used as an analytic lens (De Beer, 2016;De Beer & Mentz, 2017;Petersen, 2018). Basic qualitative study Aheto et al (2017), De Beer and Mentz (2017), Du Toit-Brits (2019), Iiyambo and Geduld (2019), Jacobs and Van Loggerenberg (1996), Kruger et al (2015), Lekalakala-Mokgele and Caka (2015), Lumina (2005), Sujee et al (2015) Bricolage Setlhodi (2019), Van Wyk (2017) Case study Du Toit et al (2016), Maistry (2009), Malan et al (2014), Orton and Nokes (2012), Terblanché (2010) Design-based research De Beer (2019b)…”
Section: Research Approaches and Designsmentioning
confidence: 99%
“…In this regard, there was research related to the use of Turnitin for writing instruction (Sujee et al, 2015) as well as the use of online assessment tools (Aheto et al, 2017). Orton and Nokes (2012) also reported on SDL within a blended learning context for an occupational health nursing course.…”
Section: Main Trends From the Corpusmentioning
confidence: 99%